2013
DOI: 10.1242/jcs.126706
|View full text |Cite
|
Sign up to set email alerts
|

FHOD1 is a combined actin filament capping and bundling factor that selectively associates with actin arcs and stress fibers

Abstract: SummaryFormins are actin polymerization factors that are known to nucleate and elongate actin filaments at the barbed end. In the present study we show that human FHOD1 lacks actin nucleation and elongation capacity, but acts as an actin bundling factor with capping activity toward the filament barbed end. Constitutively active FHOD1 associates with actin filaments in filopodia and lamellipodia at the leading edge, where it moves with the actin retrograde flow. At the base of lamellipodia, FHOD1 is enriched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 50 publications
10
95
1
Order By: Relevance
“…In fact, both scenarios could be envisioned, considering the currently known biochemical activities of FHOD1. In vitro, FHOD1 shows no actin polymerization or depolymerization activities, but acts as capping and bundling protein for actin filaments (Schonichen et al, 2013). The disordered connecting cables in FHOD1-knockdown cells could thus result from a lack of bundling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, both scenarios could be envisioned, considering the currently known biochemical activities of FHOD1. In vitro, FHOD1 shows no actin polymerization or depolymerization activities, but acts as capping and bundling protein for actin filaments (Schonichen et al, 2013). The disordered connecting cables in FHOD1-knockdown cells could thus result from a lack of bundling.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, FHOD1 has recently been shown to regulate maturation of integrin-based adhesion sites (Iskratsch et al, 2013). In vitro, FHOD1 acts as capping and bundling protein for actin filaments (Schonichen et al, 2013), although the exact biochemical activity of FHOD proteins is currently unclear . In contrast to these more accessory activities of FHOD1, INF2 has been shown to be involved in polymerization and severing of actin filaments (Gurel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The FH2 dimer nucleates filament assembly by stabilizing actin intermediates, whereas an additional processive capping activity of formins is thought to promote actin filament elongation by protecting growing barbed ends from capping proteins. Nucleation and processive elongation seem to be the major conserved activities of formins, although a number of studies also revealed additional effects on filament bundling, severing or even depolymerization (Harris et al, 2004;Harris et al, 2006;Schönichen et al, 2013). The broad range of biochemical activities suggest that formins regulate different aspects of the actin cytoskeleton architecture and actin dynamics during morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, constitutively active forms of FHOD1 inhibit actin assembly by capping growing actin filaments (Schönichen et al, 2013). Thus, the strong induction of stress fibers observed in cell transfection experiments might be the result of bundling pre-existing actin filaments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation